Joy in Ghazaliyāt-e Shams, with Reference to Gnostic Elements - Aliakbar Bagheri Khalili; Esmat Ameri (ادبیات عرفانی, 2010)
Joy is a positive state and an intrinsic part of mind.  It is a range of both material and spiritual pleasures accompanied by happiness and other positive passions. In psychology it is based on positive mindset, in sociology on sense of well-being, and in Gnosticism and religion on fulfillment of God’s will. Examination of the historical attitude to joy in the Iranian culture and literature shows that the ancient Iranians were joyful people, and Iran was considered as a land of joy and worship.  In the Sāsāniyān period due to economic downfall and weakening of religious beliefs, and other transformations and events, the specter of insecurity engulfed the country. With the formation of Ghaznavīd, and even Sāmānīd dynasties a new sense of security, as well as cultural and economic recovery emerged, but what constituted joy was essentially of an external type. However, the flourishing growth of the period did not last long and the subsequent political and social situation brought about a depressing atmosphere for the Iranians. In the same period determinism and subjectivism grew in Iran and joy took a subjective dimension to itself. Molavī, who grew up in such an atmosphere, and was under the tutelage of many scholars of the time, let joy run in his heart and reflected it in his poems. An examination of his poems shows that joy for him was of a subjective sort and concepts such as love, the beloved, and freedom from the self of fundamental importance. From Molavī’s viewpoint, love has multiple functions and the beloved gives meaning to life; thus, he endeavors to join his beloved so as to reach perfect self-actualization, and achieve everlasting joy.